PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IXe SMP NEGERI 1 SALO KABUPATEN KAMPAR - Vicry, Vadhillah Rivha Vicry Rivha; ', Zuhri D; ', Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this research is a learning process and mathematics achievement are not optimal at grade IXe Junior High School 1 Salo in the first semester academic years 2014/2015.The research was classroom action research to improve outcomes students of math lesson by implementing cooperative learning model tipe think pair square. This research consist of two cycles, and at the end of every cycle carried out mathematics achievement test. Data collected through observation and mathematics achievement test. Analysis data of observation was performed with narrative descriptive analysis and analysis data of mathematics achievement was performed with descriptive statistical analysis. Result of this research showed an increase in students from the base score with the percentage with percentage 10% to 15% on the first test and 50% on second test. Results of this research indicates that the cooperative learning tipe think pair square can improve students mathematics learning outcomes at grade IXe Junior High School 1 Salo in the first semester academic years 2014/2015. Key words: Mathematics Achievement, Cooperative learning, Think Pair Square, Class action research